The Effects of Inhaled β-Adrenergic Agonists in Transient Tachypnea of the Newborn - Esengul Keleş MD; Arzu Gebeşçe MD; Mehmet Demirdöven MD; Hamza Yazgan MD; Bülent Baştürk MD; Alparslan Tonbul MD (SAGE Publishing, 2016)
Aim . To investigate the efficacy of an inhaled β-adrenergic agonists in transient tachypnea of the newborn (TTN). Method . We retrospectively analyzed a cohort of 51 term infants (Group 1) and 37 term infants (Group 2) monitored in the newborn intensive care unit diagnosed with TTN. Infants in Group 1 received humidified oxygen alone, and infants in Group 2 were administered the inhaled β-2 agonist plus humidified oxygen. Results . TTN clinical respiratory assessment, respiratory rate, oxygen saturation values, need for supplemental oxygen therapy, blood gas PH, PO 2 , and duration of hospitalization were significantly improved in infants in Group 2 as compared with infants in Group 1 ( P < .05). No statistically significant difference was observed with regard to blood glucose, potassium, heart rate, and PCO 2 ( P > .05). Conclusion . Inhaled β-adrenergic agonist added to humidified oxygen was found to improve clinical and laboratory parameters. We believe that further studies should be conducted with larger groups to demonstrate the efficacy of β-2 agonists in TTN patients.